XRD ANALYSIS OF Bi-2212 SUPERCONDUCTORS: PREPARED BY THE SELF-FLUX METHOD - Nurmalita Nurmalita; Nailul Amani; Fauzi Fauzi (Jurnal Natural, 2013)
An experiment had been carried out on formation of Bi-2212 crystals with the self-flux method. Flux was used and derived from CuO and CaCO3. The process of synthesis was equipped with the melting process at temperature 890 °C with time variation of melting 35 minutes and 40 minutes, followed by slow cooling at a rate of 1°C/hour for 70 hours. The results were obtained and characterized by XRD test. This research aimed to produce superconducting materials with self-flux method, calculate the percentage of the value of the volume fraction, the percentage of oriented phase and impurities. Samples generated from XRD measurements were made to match with the XRD Strobell’s pattern of the superconducting Bi-2212 standards. The results showed that the value of the volume fraction of 2212 phase and the phase of the highest oriented melting at 40 minutes were equal to 67.68% and 38.89%, while the smallest impurity phase of 32.32% were obtained at the same time melting.